upaya guru dalam mengatasi kesulitan menulis pada peserta didik kelas II UPTD SD INPRES DEKOPIRA - Awo, Suratmin; Galeko, Jaka Pratama; Lapung, Jamra (Jurnal Edukasi, 2026)
"Teacher's Efforts in Overcoming Writing Difficulties Among Second Grade Students of Inpres Dekopira Elementary School." This research uses a qualitative method because the researcher aims to describe a phenomenon according to its actual condition experienced by the research subjects and present the data in the form of words. The researcher chose this type of research because they wanted to study the object's natural conditions based on observations, interviews, and documentation conducted by the researcher themselves as the key instrument. The research findings are: 1. Efforts by teachers in overcoming writing difficulties among second-grade students of Inpres Dekopira Elementary School involve teaching staff; all teachers are graduates, the curriculum used is the independent curriculum, conducting initial tests for new students who haven't registered at Inpres Dekopira Elementary School, collaborating with parents, and providing motivation and encouragement to students to foster a love of learning. 2. Challenges faced by teachers in overcoming writing difficulties include a lack of support and cooperation from parents, students experiencing writing difficulties tending to be lazy in learning, students having poor memory, unstable student psychology, and the school's limitations in providing supporting learning media.